2012
DOI: 10.1248/bpb.b11-00011
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytic Entry of <i>Legionella pneumophila</i> into Macrophages through Phosphatidylinositol 3,4,5-Trisphosphate-Independent Pathway

Abstract: Legionella pneumophila, a causative agent of Legionnaire's disease, is an intracellular pathogen. It intervenes in the signal transduction of macrophages by secreting effector molecules through the Icm/Dot type IV secretion system (T4SS). There is a connection between signaling cascades that regulate phagocytosis and the production of reactive oxygen species (ROS). Class I phosphatidylinositol 3-kinase (PI3-K) and its product phosphatidylinositol 3,4,5-trisphosphate (PI(3,4,5)P 3 ) play key roles in the reorga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…The uptake of wild-type L. pneumophila by nonpermissive murine J774A.1 macrophages or D. discoideum was partially inhibited by wortmannin or LY294002 (54, 71). In contrast, we and other groups previously found that the uptake of L. pneumophila by replication-permissive human U937 macrophages or D. discoideum occurs in a wortmannin-insensitive and PI3K-independent manner, while the uptake of an Icm/Dot mutant was strongly reduced by PI3K inhibitors (35, 72, 73). Perhaps, the conflicting results on the role of PI3Ks during L. pneumophila uptake reflect the different (permissive or nonpermissive) phagocytes and bacterial strains used.…”
Section: Discussioncontrasting
confidence: 90%
“…The uptake of wild-type L. pneumophila by nonpermissive murine J774A.1 macrophages or D. discoideum was partially inhibited by wortmannin or LY294002 (54, 71). In contrast, we and other groups previously found that the uptake of L. pneumophila by replication-permissive human U937 macrophages or D. discoideum occurs in a wortmannin-insensitive and PI3K-independent manner, while the uptake of an Icm/Dot mutant was strongly reduced by PI3K inhibitors (35, 72, 73). Perhaps, the conflicting results on the role of PI3Ks during L. pneumophila uptake reflect the different (permissive or nonpermissive) phagocytes and bacterial strains used.…”
Section: Discussioncontrasting
confidence: 90%
“…Human isolate L. pneumophila Philadelphia I (JR32), equipped with a complete dot/icm gene set encoding a type IV secretion system, which is required for intracellular amoebal growth [48], was kindly provided by Dr. Masaki Miyake of the University of Shizuoka, Japan. L. pneumophila was cultured on BCYE agar (OXOID, Hampshire, UK) at 37°C for 2 days.…”
Section: Methodsmentioning
confidence: 99%
“…These genes include one isoform of glutathione S-transferase (GST) (GenBank accession number KF784792), cytochrome c oxidase sub III (COXIII) (GenBank accession number KF784795), dynein (DYN) (GenBank accession number KF784791), synaptobrevin (SYN) (GenBank accession number KF784794) and phosphatidylinositol-3,4,5-triphosphate 3-phosphatase (PHOS) (GenBank accession number KF784793). GST is important in the detoxification of both endogenous and xenobiotic compounds and protection against oxidative stress [36][38]; COXIII is related to mitochondrial metabolism, including ATP production and reactive oxygen species (ROS); DYN is a motor protein involved in the conversion of chemical energy present in molecules of ATP into mechanical energy along microtubules and is involved in intracellular trafficking pathways [39]; SYN is a v-SNARE protein that participates in the exocytosis of proteins [40][42]; and phosphatidylinositol-3,4,5-trisphosphate 3-phosphatase plays an important role in the reorganization of the cytoskeleton, NADPH production and ROS production [43].…”
Section: Resultsmentioning
confidence: 99%